PERILAKU GESER BALOK KOMPOSIT CASTELLATED BUKAAN HEKSAGONAL DENGAN SELIMUT MORTAR - , DWIATMAJA PRADIPTA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The WF profile steel beam covered with concrete has been the well-known composite structure application. Nevertheless, other than resulting in increasing section capacity, it also induces increasing material weight. One of the alternatives to cope with the problems is the use of castellated beam, with its excellences in increasing the moment capacity as well as overcoming the problem caused by castellated beam, such as web buckling and decreasing shear capacity. The objective of this study is to observe the shear behavior of castellated composite beam with hexagonal opening and mortar blanket. The tests were given to three beams with 865 mm span. One castellated beam (BC1) was made from WF 150x75x5x7 profile and enhanced into WF 225x75x5x7. One castellated beam was with lateral stiffener below the load position (BC2) and the other was covered with mortar blanket (BCK). The mortar mixture used was made in weight ratio of 1:1,5